Comparative Evaluation of Agroindustrial Byproducts for the Production of Alkaline Protease by Wild and Mutant Strains of Bacillus subtilis in Submerged and Solid State Fermentation - Hamid Mukhtar; Ikramul Haq (The Scientific World Journal)
The present study describes the screening of different agroindustrial byproducts for enhanced production of alkaline protease by a wild and EMS induced mutant strain of Bacillus subtilis IH-72EMS8. During submerged fermentation, different agro-industrial byproducts were tested which include defatted seed meals of rape, guar, sunflower, gluten, cotton, soybean, and gram. In addition to these meals, rice bran, wheat bran, and wheat flour were also evaluated for protease production. Of all the byproducts tested, soybean meal at a concentration of 20 g/L gave maximum production of the enzyme, that is, 5.74  ±  0.26 U/mL from wild and 11.28  ±  0.45 U/mL from mutant strain, during submerged fermentation. Different mesh sizes (coarse, medium, and fine) of the soybean meal were also evaluated, and a finely ground soybean meal (fine mesh) was found to be the best. In addition to the defatted seed meals, their alkali extracts were also tested for the production of alkaline protease by Bacillus subtilis, but these were proved nonsignificant for enhanced production of the enzyme. The production of the enzyme was also studied in solid state fermentation, and different agro-industrial byproducts were also evaluated for enzyme production. Wheat bran partially replaced with guar meal was found as the best substrate for maximum enzyme production under solid state fermentation conditions.